Downregulation of serum miR-26a predicts poor clinical outcome of papillary thyroid carcinoma - Ren, Guanghui (Int J Clin Exp Pathol, 2017)
Deregulation of miRNAs has been demonstrated to play an important role in the initiation and development of many types of cancers including papillary thyroid carcinoma (PTC). Currently the role of miR-26a and its potential clinical significance for PTC remains unknown. Eighty-four PTC patients and forty healthy controls were enrolled in this study. Quantitative real-time PCR (qRT-PCR) was performed to determine the expression level of serum miR-26a in all the participants. The association between serum miR-26a expression level and clinical outcome of PTC was investigated. Serum miR-26a expression level was reduced in PTC patients compared with the healthy controls (P<0.01) and significantly increased after receiving treatments (P<0.01). Serum miR-26a expression level was associated with lymph node metastasis (P=0.0173) and TNM stage (P=0.0022). In addition, PTC with lower serum miR-26a expression had poorer overall (P=0.029) and disease free survival rates (P=0.0004). Moreover, serum miR-26a expression was an independent risk factor for PTC (P<0.05). Collectively, down-regulation of serum miR-26a is associated with poor prognosis in PTC and it might be a promising biomarker for this malignancy.